(untitled) (Progressive Agriculture, 2013)
This paper examines the factors influencing collective action for common resource management. As information base, data sets of 44 brackish water shrimp farming communities in Bangladesh have been used. The result shows that collective action is associated with resource scarcity, market distance from the resource, group size, heterogeneity in the community, and involvement of other institutions. The results tell that while graduates facilitate, outsiders impede collective action. Unlike the findings from other sources, distance to market place has been found very important for common resource management in Bangladesh. Collective action could be more successful, when water user groups are founded through users self motivation, receiving coordination help and technical support from governmental institutions. DOI: http://dx.doi.org/10.3329/pa.v22i1-2.16477 Progress. Agric. 22(1 & 2): 151-168, 2011